A standardized Hippophae extract (SBL-1) counters neuronal tissue injuries and changes in neurotransmitters: implications in radiation protection - Madhu Bala; Vanita Gupta; Jagdish Prasad (Taylor & Francis Group, 2017)
Context: Effects of a radioprotective, standardized leaf extract (code SBL-1) from traditional medicinal plant, sea buckthorn [Hippophae rhamnoides L. (Elaeagnaceae)], on neurotransmitters and brain injuries in rats showing radiation-induced conditioned taste aversion (CTA), are not known. Understanding CTA in rats is important because its process is considered parallel to nausea and vomiting in humans. Objective: This study investigated the levels of neurotransmitters, antioxidant defences and histological changes in rats showing radiation CTA, and their modification by SBL-1. Materials and methods: The inbred male Sprague-Dawley rats (age 65 days, weighing 190 ± 10 g) were used. Saccharin-preferring rats were selected using standard procedure and divided into groups. Group I (untreated control) was administered sterile water, group II was 60Co-γ-irradiated (2 Gy), and group III was administered SBL-1 before irradiation. Observations were recorded up to day 5. Results: Irradiation (2 Gy) caused (i) non-recoverable CTA (≥ 64.7 ± 5.0%); (ii) degenerative changes in cerebral cortex, amygdala and hippocampus; (iii) increases in brain dopamine (DA, 63.4%), norepinephrine (NE, 157%), epinephrine (E, 233%), plasma NE (103%) and E (160%); and (iv) decreases in brain superoxide dismutase (67%), catalase (60%) and glutathione (51%). SBL-1 treatment (12 mg/kg body weight) 30 min before irradiation (i) countered brain injuries, (ii) reduced CTA (38.7 ± 3.0%, day 1) and (iii) normalized brain DA, NE, E, superoxide dismutase, catalase and CTA from day 3 onwards. Discussion and conclusion: Radiation CTA was coupled with brain injuries, disturbances in neurotransmitters and antioxidant defences. SBL-1 pretreatment countered these disturbances, indicating neuroprotective action.